High-Performance Mathematical Models for the Analysis of Single Line-to-Ground Faults in Medium Voltage Electrical Networks - Toader , Dumitru; Greconici, Marian; Vesa, Daniela; Tatai , Ildiko (Techniques and Innovation in Engineering Research Vol. 9, 2023)
Setting the protections is essential to correctly and quickly detect faulty power lines. A correct setting requires the use for the calculation of the measured quantities in order to detect faults of mathematical models that reproduce as accurately as possible the behavior of electrical networks during faults. In the case of medium-voltage electrical networks, the defect that occurs most frequently in their operation is that of the single line-to-ground type. The sizes characterizing such a fault are strongly influenced by the method used to connect the neutral of the medium voltage network to the ground, by the condition of the insulation of the medium voltage network as well as by the value of the resistance at the location of the fault. The paper analyzes how active power losses from the insulation of the medium voltage network (insulation loss angle \(δ\)), the value of the resistance at the fault location (Rf ), and the method used to connect the neutral of the medium voltage network to the ground influence the value the fault current, the currents of the non-faulted lines and the zero-sequence voltage related to the medium voltage bus-bars in the transformer substation. The conditions are established in which the insulation of the medium voltage network can be considered perfect (insulation loss angle \(δ\) = 0) depending on the method used to connect the neutral of the medium voltage network to the ground, the value of the transition resistance at the fault location and the regime in which the medium voltage network operates. In the analysis made, real medium voltage electrical networks were considered, and the results obtained using the proposed mathematical models were verified experimentally in the same medium voltage electrical networks.